Noise exposure in an opencast platinum mine in the Limpopo Province during 2006-2010 - Van Coller, Petrus Paulus Johannes (My University, 2015)
Background: Tasks aimed at increasing productivity in the opencast mining industry have indicated a need to use larger machinery together with improvements in technology. This has resulted in an increase in the use of mechanical products, which has been accompanied by an increase in occupational noise exposure levels. Dangerous occupational noise exposures might be more prevalent in the mining sector than in other industrial segments due to a large number of persons employed by the mining sector. However, given the scant literature on occupational noise exposure in opencast mines, we are unsure of the magnitude of the problem. Therefore, it is imperative to conduct a research study on occupational noise exposures in an Opencast Platinum Mine and to provide recommendations on the abatement of noise exposure to workers to mine management. Aim: This study aimed to determine if employees in the production area of an Opencast Platinum mine were over-exposed to noise levels above acceptable national and international exposure limits of 85dB(A) and 90dB(A) respectively during 2006-2010. Objectives: The main study objectives were to identify and assess occupations with significant risk to occupational noise exposure in an Opencast platinum mine production area during 2006-2010; to describe personnel noise exposure amongst the identified significant risk occupations in the same Opencast Platinum mine production area during 2006-2010. Finally, the study compared occupational noise exposure of identified significant risk occupations in the same Opencast Platinum mine production area with national and international exposure limits during 2006-2010. Methodology: The study employed a cross sectional retrospective record review of noise measurement data collected during a 5-year period. Statistical analyses were conducted using S-PLUS (version 8.1) and SAS System Software packages (version 9.1). To describe the measures of central similarity and distribution of the noise levels, arithmetic mean (AM) median, geometric means (GMs) and geometric standard deviations were presented in tables. Results: During the hazard identification process ten occupations were identified as significant noise risk exposed occupations, the shovel operator was the lowest exposed occupation with a minimum noise level measurement of 78.40dB (A) (TWA.8h) and maximum-noise level of 96.95dB (A) (TWA.8h). The drill rig operator was one of the top 3 most exposed occupations with a 90th percentile of 98.13dB (A) (TWA.8h). The drill foreman with a maximum of 99.75 dB (A) and a 90th percentile of 96.93dB (A) (TWA.8h) exceed the South African Department of Minerals and Resources (DMR) OEL of 85dB (A) (TWA.8h). From the total amount of three thousand one hundred and sixty (3160), ninety eight percent (98.92%) of the measured time weighted 8 Noise Exposure in an Opencast Platinum Mine in theLimpopo Province during 2006 – 2010 hours average (TWA.8h) results exceed the South African Department of Minerals and Resources (DMR) OEL of 85dB (A) , 65% exceeded the Occupational Health and Safety Administration (OHSA) PEL of 90dB(A) for noise. The front-end loader operator had the highest percentage of measurements (81.65%) exceeding the Occupational Health and Safety Administration (OHSA) PEL of 90dB (A) for noise exposure in the time frame 2006-2010. Conclusions: This study showed that there is substantial risk for overexposure to noise in occupations working in the production area of an opencast mine. Task type and duration associated with production in the opencast mine may determine whether employees are exposed to noise > 85dB (A) (TWA.8h). Hence equipment type, maintenance of controls and employee risk reduction behaviour may be important elements of noise exposure. Identifying noise exposure elements and contributing sources will be of value when improving or implementing a new control at the noise source. Development of methodical and comprehensive hearing conservation programme for lowering the noise level in workplaces and prevention of occupational noise induced hearing loss, at the place of work is suggested.
A research report submitted to the Faculty of Health Sciences; School of Public Health; University of Witwatersrand; Johannesburg in fulfilment of the requirements for the degree of Master in Public Health in the field of Occupational Hygiene Johannesburg; May 2015